2019
DOI: 10.1155/2019/7190596
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Helicobacter pylori Infection and Plasmacytoid and Myeloid Dendritic Cells in Peripheral Blood and Gastric Mucosa of Children

Abstract: Purpose To investigate the frequency and activation status of peripheral plasmacytoid DCs (pDCs) and myeloid DCs (mDCs) as well as gastric mucosa DC subset distribution in Helicobacter pylori- (H. pylori-) infected and noninfected children. Materials and Methods Thirty-six children were studied; twenty-one had H. pylori. The frequencies of circulating pDCs (lineage−HLA-DR+CD123+) and mDCs (lineage−HLA-DR+CD11c+) and their activation status (CD83, CD86, and HLA-DR expression) were assessed by flow cytometry. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Although limited studies have been performed ton this topic to date, several authors emphasized the role of H. pylori in modifying the host's immune responses to this infection. Thus, Helmin-Basa recently underlined the lack of mature CD83+ in the gastric tissue samples of children with H. pylori infection, hypothesizing that this peculiarity might enable tolerance to local antigens, decreasing the inflammatory responses [121]. Previous studies of our team supported the implications of innate immunity in promoting or suppressing H. pylori infection in children, revealing the contribution of certain TLR polymorphisms like TLR2 rs3804099 and TLR9 rs352140, as well as of inflammasomes (NLRP3 rs10754558), in augmenting inflammation as a response to this infection [2] (Table 2).…”
Section: H Pylori Infection and Gastric Carcinogenesis Hallmarks In C...mentioning
confidence: 99%
“…Although limited studies have been performed ton this topic to date, several authors emphasized the role of H. pylori in modifying the host's immune responses to this infection. Thus, Helmin-Basa recently underlined the lack of mature CD83+ in the gastric tissue samples of children with H. pylori infection, hypothesizing that this peculiarity might enable tolerance to local antigens, decreasing the inflammatory responses [121]. Previous studies of our team supported the implications of innate immunity in promoting or suppressing H. pylori infection in children, revealing the contribution of certain TLR polymorphisms like TLR2 rs3804099 and TLR9 rs352140, as well as of inflammasomes (NLRP3 rs10754558), in augmenting inflammation as a response to this infection [2] (Table 2).…”
Section: H Pylori Infection and Gastric Carcinogenesis Hallmarks In C...mentioning
confidence: 99%
“…Interestingly, pDCs from H. pylori-infected patients already showed alterations. Patients infected with H. pylori exhibited elevated HLADR expression on circulating pDCs compared to those without H. pylori infection [ 89 ]. Additionally, a higher density of pDCs was observed in the gastric mucosa [ 89 ].…”
Section: Plasmacytoid Dendritic Cells In Various Gastrointestinal Can...mentioning
confidence: 99%
“…Patients infected with H. pylori exhibited elevated HLADR expression on circulating pDCs compared to those without H. pylori infection [ 89 ]. Additionally, a higher density of pDCs was observed in the gastric mucosa [ 89 ]. Moreover, it was demonstrated that within the tumor microenvironment of GC, there is a positive correlation between H. pylori infection and the expression of TLR9 and ICOS-L on pDCs [ 90 ].…”
Section: Plasmacytoid Dendritic Cells In Various Gastrointestinal Can...mentioning
confidence: 99%
“…As it is well known, H. pylori infection is associated with GC initiation, which leads to active inflammation and immune responses including the changes of pDCs. One study compared pDCs in H. pylori -infected children and noninfected controls and demonstrated upregulated expression of HLA-DR on circulating pDCs, and increased density of pDCs in gastric epithelium mucosa in H. pylori -infected children ( 89 ). Gastric mucosal microbiota analysis from 64 GC patients showed that the diversity, composition, and function of gastric mucosal microbiota was significantly different in tumor tissues compared with normal and peritumoral tissues, and BDCA2 + pDCs and Foxp3 + Tregs were positively correlated from different microhabitats ( 70 ).…”
Section: Immunobiology Of Pdcsmentioning
confidence: 99%